Experimental determination of the dispersion of ions from a point source in the environment. Issue 10 (29th April 2019) - Jayaratne, E. R.; Ling, X.; Pushpawela, B.; Morawska, L.
ABSTRACT: The dispersion of ions from a point source has been extensively modelled but there have been very few attempts to experimentally verify the theoretical findings. The main reason for this has been the difficulty of discriminating between cluster ion and charged particle concentrations in the air. In this paper, we describe a novel technique for the experimental determination of the dispersion of ions from a point source in air. Laboratory experiments showed that the lifetime of cluster ions in an aerosol cloud was of the order of minutes. However, once they attached to aerosols, the particles retained the charge for at least 30 min, suggesting that they may be carried long distances in natural winds. A negative air ionizer was used to produce ions and charged particles in an open field in the presence of a steady horizontal wind. A neutral cluster and air ion spectrometer was used to measure cluster ion and charged particle concentrations as a function of downwind distance from the source. The results are broadly consistent with the Gaussian dispersion model for a continuous point source. We estimate that cluster ions can be carried up to a distance of several hundred metres before they fully attach to particles which can then be carried as far as 3–4 km. Therefore, these observations have important bearing on exposure to cluster ions and charged particles downwind of ion sources such as high voltage power lines and busy roads.